Implementasi Hak Servituut pada Pelaksanaan Pendaftaran Tanah Sistematis Lengkap di Kabupaten Bekasi - Ishaya, Nugraha Salman; Budhiawan, Haryo; Widarbo, Koes (Sekolah Tinggi Pertanahan Nasional, 2021)
The Ministry of ATR/BPN organizes land registration innovations based on the national strategic program, namely PTSL. The implementation of PTSL aims at accelerating land registration in a fair and equitable manner, including anticipating disputes in the field of utilization and spatial planning. One important issue is the dispute over road access. The Land Office of Bekasi Regency applies a policy of implementing servituut rights in land registration activities as an anticipation of disputes related to road access. This research was conducted to understand the implementation of servituut rights as the actualization of the social function of land in the PTSL program at the Bekasi Regency Land Office. This study uses empirical legal research methods. The results of the research show that the implementation of the servituut rights policy is motivated by the dualism of road status, the existence of regional development and land acquisition, and the relatively high land value. The implementation of the policy has undergone a change in meaning, from restrictions on land use to the obligation to surrender some land rights. For PTSL participants who agree to give up part of their rights for roads, the administration of the transfer of rights is carried out in a Declaration Letter on Land Boundaries and Land Areas. For those who disagree, the plot of land is included in the K3 category and a land register is made.